“Recognizable” Textiles In Daily Practices Of The 16th-Century Florence - Гоцало, Катерина (Київський національний університет імені Тараса Шевченка, 2020)
The aim of the article is to shape the semiotic of textiles in the context of their use in various daily practices of the city of Florence during the 16th century. The article investigates the possibility of different representatives of the city to perceive fabrics as a symbol and the ability to identify different types of textiles “by eye”. It consists of three thematic sections. The first one dedicates to the study of those characteristics of textiles that were decisive in the formation of their semiotics. We have found that fabric materials and techniques were such characteristics. Since the creation of textiles was a complicated process, their function as a symbol of user’s status was extremely important. The second part devotes to those manufacturing processes within cities that facilitated exchange of technology and design of fabrics and, as a consequence, perception by users such a textile component as an ornament. The third part of the article deals with specific examples of the Florentine comprehension of certain fabrics. It draws attention to the way textiles are described in written sources. The various urban practices have made it possible for representatives of different segments of the population to be able to distinguish different types of textiles. Fabrics have become an additional way of identifying the status and origin of their user. The ornaments were also symbolic, depending on the materials used to make them. On the other hand, many city dwellers could not identify elements of most common fabric patterns and, therefore, could not perceive them as symbols.

Метою статті є формування семіотики текстилю в контексті його використання в повсякденних практиках міста Флоренція протягом XVI ст. Досліджена можливість різних представників міста сприймати тканини в якості символу та вміння ідентифікувати різні види текстилю «на око». Стаття складається з трьох тематичних частин. Перша присвячена вивченню тих характеристик тканин, які були визначальними у формуванні їх семіотики. Було з’ясовано, що матеріали та техніки виготовлення текстилю слугували такими характеристиками. Так як створення тканин було кропітким процесом, їх функція в якості символу статусу користувача була винятково важливою.  Друга частина присвячена тим виробничим процесам в межах міст, які сприяли обміну технологіями та дизайнами тканин, а як наслідок, сприйняттю користувачами текстилю такої його складової як орнамент. В третій частині статті розглядаються конкретні приклади  перцепції самими флорентійцями тих або інших тканин. Звертається увага на те, яким чином описувався текстиль в різних писемних джерелах. Різноманітні міські практики сприяли тому, що представники різних верств населення вміли розрізняти види текстилю. Тканини ставали допоміжним способом для ідентифікації статусу та походження їх носія. Орнаменти, залежно від матеріалів, використаних для їх виготовлення, також були символічними. З іншого боку, окремі елементи більшості поширених візерунків на тканинах не сприймалися в якості символів та не могли бути ідентифіковані міськими мешканцями.
«Впізнавані» тканини в повсякденних практиках Флоренції XVI ст.
Keywords: textiles; Florence; 16th c.; symbolism; ornament; текстиль; Флоренція; XVI ст.; символіка; орнамент